(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The author of this article discusses the significance of error correction and the criteria which have been put in order to correct students in more positive way rather than discouraging them from making one. Additionally, both teachers and students should understand the importance of corrective feedback and noticing mistakes.